2011
DOI: 10.1017/s1352465811000464
|View full text |Cite
|
Sign up to set email alerts
|

Applying Mindfulness Therapy in a Group of Psychotic Individuals: A Controlled Study

Abstract: Both the usefulness and effectiveness of implementing a mindfulness-based program have been replicated in a controlled manner in patients with psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 5 publications
3
70
0
4
Order By: Relevance
“…About 1,250 records were removed after screening the relevance of article titles and abstracts to the topic of the review. The full texts of the remaining 21 studies were reviewed and finally 15 studies were excluded after full review, leaving behind only six studies [17][18][19][20][21][22] to be included for this review. Details of the searching process are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 1,250 records were removed after screening the relevance of article titles and abstracts to the topic of the review. The full texts of the remaining 21 studies were reviewed and finally 15 studies were excluded after full review, leaving behind only six studies [17][18][19][20][21][22] to be included for this review. Details of the searching process are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…In the six randomized controlled studies, two were pre-and post-test design 20,21 and the other studies (n= 4) [17][18][19]22 used repeated-measures design with varying follow-up periods from 6 months 17 to 2 years 22 .…”
Section: Design Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were no differences between groups, improvements were observed in clinical functioning (conceptualised as subjective well-being, problems and symptoms, life functioning, and risk) and mindfulness of distressing thoughts and images. Langer et al (2012) found that no significant effects were observed in any measure between the groups, except in mindfulness response to stressful thoughts and images within the Mindfulness-Based Cognitive Therapy group (eight individual sessions). Chien and Lee (2013) found that Mindfulness-based Psychoeducation (MBP-12 group sessions) was associated with significant change in symptom sever-ity, illness insight, and length of re-hospitalisation at post-intervention, while functioning and number of re-hospitalisations improved significantly only at the 18-month follow-up.…”
Section: Mindfulness-based Interventionsmentioning
confidence: 74%
“…(7) Psychotic disorders have also been treated with mindfulness techniques, even if some clinicians have expressed reservations about using such methods with this group of patients (Shonin et al 2014). The results of these studies, however, are encouraging (Khoury et al 2013), especially in group settings (Chadwick et al 2005;Gumley et al, 2010;Braehler et al 2012, Langer et al 2012. (8) Finally, an increasingly important field of research is sexual disorders and their treatment through mindfulness (Brotto et al 2008;Silverstein et al 2011).…”
Section: Research Findings and Research Dilemmasmentioning
confidence: 99%